The Relationship of Facial Soft Tissue A’N’B Angle and Facial Hard Tissue ANB Angle in Determination of Skeletal Relations - Shella Indri Novianty; Vena Tria Melynda; Mohammad Yusuf; Rama Putranto (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Cephalometric analysis used in orthodontics to informs the diagnosis, treatment planning, quantifies changes during treatment, and provides data for clinical research. It has been used for determination of Skeletal Relations using facial hard tissue ANB Angle. Points A and B on the facial hard tissue correlate closely with the positions of the corresponding points on the soft tissue. This study aims to determine the relationship between the A'N’B angle of soft tissue and the ANB angle of hard tissue in determining the class of skeletal relations Method: The sample used in this study was 75 cephalograms, which had been selected according to the criteria. Cephalometric tracing is done manually. Inter-observer and intra-observer measurements were carried out to increase the validity and reliability of the research instrument. The Bland-Altman method is used as a statistical fit test. The results of the research data were then tested for normality with the Kolmogorov-Smirnov test. For further testing to test the significance of the correlation coefficient obtained in the Pearson test, the significance test of the t-test is used. Result: The results of t-count > t-table, which means that there is a strong linear relationship between hard tissue ANB and soft tissue A'N’B with a correlation coefficient (r) > 0.05. Conclusion: The soft tissue A'N'B' angle can be used as an alternative in determining the class of skeletal relationships in addition to the hard tissue ANB angle